(untitled) (Revista Educação, Artes e Inclusão, 2021)
The teaching and learning processes for deaf students have reached higher and better levels in the educational field in recente years, but the challenges are still prevalent. This research aimed to evaluate the strategies of teaching physics to deaf students based on documents already published. For this, a systematic review of the literature on the topic was carried out, and the search was limited to articles published between the years 2014 and 2019 from the Scientific Electronic Library Online (SciELO) and Google Scholar databases, with the following descriptors: 1) teaching; 2) Physics; 3) deaf; 4) inclusion; and 5) Pounds. It was evaluated how the teaching of Physics for the deaf student is treated, from the perspective of integral and omnilateral human formation, based on the authors Karl Marx and Gramsci. After evaluating the articles, it is observed that the teachers show interest and/or concern in the insertion of the deaf student in the discipline of Physics. Thus, the study points out factors that influence the insertion process of deaf students, such as insuficiente financial resources, lack of specialized professionals in the area of inclusive education to assist teachers and the need for continuing education by education professionalsin general.